Presoja (ne)ustreznosti Enotne metodologije za ugotavljanje vrednosti gozda kot strokovne osnove za cenitev gozdov - Šinko, Milan (Gozdarski vestnik, 2008)
In the article we analyze the Uniform Method for Agricultural Land and Forest Value Determination (1987) from the viewpoint of the evaluated compensation. The analysis showed the discordance with the regulations of the valid legislature in the field of expropriations and compensations and questionability of the hypothesis that the compensation should enable foundingof a new forest. The uniform methodology does not enable the calculation of an appropriate compensation for older forests expropriation, because the applied approach is not based on the market conditions and collateral damage.
Keywords: gozdovi; cenitev; razlastitev; odškodnine; zakonodaja; metodologije